Avaliação em role-play no contexto do ensino do Direito - Pinto Sica, Ligia Paula Pires (2011)
Since the development of certain skills of a Law student is directly related to the study and improvement of the debate about active learning methods, as well as the role of evaluation in the application of these, this work intended to contribute to the debate about the teaching of law through role-play, emphasizing that the evaluation of the student is part of this process. Thus, the paper addresses the issue of assessment and the teaching method known as role-play in these two aspects: (i) the suitability of the method to the teaching of Law and (ii) tools for assessment of student when applying the role-play, and the role of the teacher as an evaluator. Some assessment tools were also appointed in order to demonstrate that different types of assessment may be required when applying different teaching methods. The choice among them will depend on the didactic purpose proposed by the professor and/or the activity that has to be carried out. This idea turns away from the idea of evaluation as a simple tool to assess the results of the individual or collective student learning.